(untitled) (Itinera, 2024)
Orazio Costa, theater director and teacher for over thirty years at the National Academy of Dramatic Arts in Rome, is the author of a pedagogical system called mimic method. It consisted of a theory and a practice aimed at revitalizing the concept of mimesis. The practice included exercises on identification with natural phenomena, necessary for staging dramas respectful of human nature and poetic inspiration. While Avant-gardes rejected art as imitation of an object, and the new theatrical forms refused the value of the dramaturgical text within the performance, Costa defended the role of literature and the representation of human events in the theatrical ritual. Despite the accusations of traditionalism, his idea of mimesis is absolutely in line with the twentieth- century reception of the notion. Like authors such as Benjamin, Adorno, Ricoeur, the director has analyzed mimesis as an innate behavior, and he based his aesthetic positions on this conception. For Costa, art is the wonderful metaphor of the encounter between the individual and nature, which pushes towards forms of expressions comprehensible to the community.